The Use of Information Gap Activity to Improve Speaking Ability of the Second Year of SMPN 34 Pekanbaru In Making Information Questions - Randha, Opny Vitia Randha Vitia; Nababan, M. Nababan; ', Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is a classroom research that was conducted based on the problem occurred at the eighth grade students of SMP 34 Pekanbaru at studying the improvement on the ability of the eighth grade students of SMP 34 Pekanbaru in speaking in making information questions. Besides, knowledge in making information questions is mostly improved after being taught by information gap activity method. The participants were 34 students from VIII 2 of SMP 34 Pekanbaru. This research was conducted in two cycles. The data collection technique was obtained through (1) observation sheet which was applied to know the students and teacher performance during the teaching and learning process, (2) test was done to measure students’ achievement, and (3) field note was obtain information about teacher, the students activities and performance in the teaching and learning process during the implementation of picture series. The research finding can briefly explain as follow: first the student’s students speaking ability could be improved by using information gap activity method. Before the research was done, the average score of students was only 35.92 in pretest. After the research was done for cycle 1, it improved to77.19. Then, In cycle 2 increased up to 85.5. The observation sheet and field note result showed that the used of information gap activity make the teaching process more effective and it also helped students’ improve their speaking ability and more active in learning process. This improvement happened because this information gap activity method is appropriate to be applied to the class.Keyword: information gap activity, information questions, students’ speaking ability